Reversibility of Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis - Speyer, Helene; Westergaard, Casper; Albert, Nikolai; Karlsen, Mette; Stürup, Anne Emilie; Nordentoft, Merete; Krogh, Jesper (Frontiers in Endocrinology, 2021)
Background and Aims Weight gain is a major adverse effect of antipsychotic medication, negatively affecting physical and mental well-being. The objective of this study was to explore if dose reduction, discontinuation, switch to a partial agonist, or switch from polypharmacy to monotherapy will lead to weight loss. Methods Controlled and uncontrolled studies reporting the effects of discontinuation, dose reduction, switch to a partial agonist, or switch from polypharmacy to monotherapy on weight were included. Primary outcome was difference in weight compared to maintenance groups based on controlled studies. Secondary outcome was change in weight from initiation of one of the included interventions until follow-up in a pre-post analysis. Results We identified 40 randomized controlled trials and 15 uncontrolled studies including 12,279 individuals. The effect of the interventions, i.e. dose reduction, drug discontinuation, or switch to a partial agonis, reduced the weight with 1.5 kg (95% CI −2.03 to −0.98; P < 0.001) compared to maintenance treatment. The weight change from pre to post was a reduction of 1.13 kg (95% CI −1.36 to −0.90; P < 0.001). Conclusion We found a significant but small reduction in weight, suggesting that antipsychotic-induced weight gain can be reversed to some degree. Only a few studies were designed to address the question as primary outcome, which limits the generalizability of our findings.